Comparative effectiveness of two adalimumab biosimilars in 1318 real-world patients with inflammatory rheumatic disease mandated to switch from originator adalimumab: nationwide observational study emulating a randomised clinical trial. Issue 11 (29th April 2021) - Nabi, Hafsah; Georgiadis, Stylianos; Loft, Anne Gitte; Hendricks, Oliver; Jensen, Dorte Vendelbo; Andersen, Marlene; Chrysidis, Stavros; Colic, Ada; Danebod, Kamilla; Hussein, Mohamad Redha; Kalisz, Maren Høgberget; Kristensen, Salome; et al.
Abstract : Objectives: In 2018, a nationwide mandatory switch from originator to biosimilar adalimumab was conducted in Denmark. The available biosimilar was GP2017 (Hyrimoz) in Eastern regions and SB5 (Imraldi) in Western regions. We aimed to assess the comparative effectiveness of GP2017 versus SB5 in patients with rheumatoid arthritis (RA)/psoriatic arthritis (PsA)/axial spondyloarthritis (AxSpA). Methods: Observational cohort study based on the DANBIO registry with geographical cluster pseudo-randomisation, analysed by emulating a randomised clinical trial. Main outcome was adjusted 1-year treatment retention (Cox regression). Furthermore, 6 months' remission rates (logistic regression), reasons for withdrawal and back-switching to originator were investigated (overall and stratified by indication). Results: Overall, of 1570 eligible patients, 1318 switched and were included (467 RA/321 PsA/530 AxSpA); 623 (47%) switched to GP2017, 695 (53%) to SB5. Baseline characteristics of the two clusters were largely similar, but some differences in registration practice were observed. The combined 1-year retention rate for the two biosimilars was 89.5%. Compared with SB5, estimated risk of withdrawal for GP2017 was lower (HR 0.60; 95% CI 0.42 to 0.86) and 6 months' remission rate was higher (OR 1.72; 95% CI 1.25 to 2.37). Stratified analyses gave similar results (statistically significant for RA). During 1 year, 8.5% and 12.9% withdrew GP2017 and SB5, respectively (primarily lack of effect and adverse events), of whom 48 patients (3.6%) back-switched. Conclusion: This head-to-head comparison of GP2017 versus SB5 following a mandatory switch from the originator indicated differences in effectiveness in routine care. This may reflect a true difference, but other explanations, for example, differences in excipients, differences between clusters and residual confounding cannot be ruled out.